Mucoadhesive Hydrogel Films of Econazole Nitrate: Formulation and Optimization Using Factorial Design. (10th June 2014) - Gajra, Balaram; Pandya, Saurabh S.; Singh, Sanjay; Rabari, Haribhai A.
Abstract : The mucoadhesive hydrogel film was prepared and optimized for the purpose of local drug delivery to oral cavity for the treatment of oral Candidiasis. The mucoadhesive hydrogel film was prepared with the poly(vinyl alcohol) by freeze/thaw crosslinking technique. 3 2 full factorial design was employed to optimize the formulation. Number of freeze/thaw cycles (4, 6, and 8 cycles) and the concentration of the poly(vinyl alcohol) (10, 15, and 20%) were used as the independent variables whereas time required for 50% drug release, cumulative percent of drug release at 8th hour, and "k " of zero order equation were used as the dependent variables. The films were evaluated for mucoadhesive strength, in vitro residence time, swelling study, in vitro drug release, and effectiveness against Candida albicans . The concentration of poly(vinyl alcohol) and the number of freeze/thaw cycles both decrease the drug release rate. Mucoadhesive hydrogel film with 15% poly(vinyl alcohol) and 7 freeze/thaw cycles was optimized. The optimized batch exhibited the sustained release of drug and the antifungal studies revealed that the drug released from the film could inhibit the growth of Candida albicans for 12 hours.